Correction: Exploring the potential antimalarial properties, safety profile, and phytochemical composition of Mesua ferrea Linn. - Atthaphon Konyanee; Prapaporn Chaniad; Arisara Phuwajaroanpong; Walaiporn Plirat; Parnpen Viriyavejakul; Abdi Wira Septama; Chuchard Punsawad (PLoS ONE, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0312047.].